Analisis Sentimen Terhadap Komentar Video Youtube Menggunakan Support Vector Machines - Toif Muhayat; Ahmad Fauzi; Jamaludin Indra (STMIK Banjarbaru, 2023)
Many Youtube users leave comments on the YouTube video content they watch. These comments would be useful if further analysis were carried out. This study aims to analyze Sentiments Toward Youtube Video Comments, to make it easier for creators to find out what types of videos are of interest to viewers, without having to read the comments one by one. The stages carried out in this research are web scrapping, preprocessing, labeling, feature extraction, classification and evaluation. The results of the analysis show that the type of video content with the theme of daily vlogs is more in demand by YouTube users with positive dominant sentiment results. The daily vlog theme has a positive sentiment of 84.0% and a negative sentiment of 16.0%. The use of the SVM (Support Vector Machine) algorithm has an accuracy value of 86%, a precision of 87%, a recall of 99% and an f1-score of 100%.Keywords: Sentiment Analysis; Text Mining; Support Vector Machine; Youtube AbstrakBanyak pengguna Youtube yang meninggalkan komentar pada konten video youtube yang mereka tonton. Komentar-komentar tersebut akan memberikan manfaat jika saja dilakukan analisis lebih lanjut. Penelitian ini bertujuan menganalisis Sentimen Terhadap Komentar Video Youtube, untuk memudahkan kreator mengetahui jenis video yang diminati penonton, tanpa harus membaca komentar secara satu per satu. Tahapan yang dilakukan dalam penelitian ini adalah web scrapping, preprocessing, labelling, ekstraksi fitur, klasifikasi dan evaluasi. Hasil analisis menunjukkan jenis konten video bertema daily vlog lebih banyak diminati oleh pengguna youtube dengan hasil sentimen dominan positif. Tema daily vlog memiliki sentimen positif sebesar 84.0% dan sentimen negatif sebesar 16.0%. Penggunaan algoritma SVM (Support Vector Machine) memiliki nilai akurasi sebesar 86%, presisi sebesar 87%, recall sebesar 99% dan f1-score sebesar 100%.Kata Kunci: Analisis Sentimen; Text Mining; Support Vector Machine; Youtube